Sistem Stemming Otomatis untuk Kata dalam Bahasa Indonesia - Rila Mandala; Erry Koryanti; Rinaldi Munir; Harlili Harlili (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Stemming is a process to restore words to its base form, by stripping each word fromits derivational and affixes. A stemming process has an important role for machinetranslationand other computational lingustics area. In Malaysian there is a stemmingalgorithm that has been developed and tested for application in information retrieval which isknown as Othman algorithm. There are several differences of Bahasa Indonesia’smorphology and Malay’s morphology, so The Othman algorithm can not be applied directlyin bahasa Indonesia. Furthermore, the accuracy of Othman algorithm also is not good. Thispaper proposes some modifications from Othman algorithm. The modifications includes,various stemming procedures, rule of affixes, and dictionary of root words. Experiments showthat Our modification method has a better accuracy in stemming Bahasa Indonesia’s words.Keywords: stemming, word-lemmatization, affix-stripping